Yucatecan regionalism vis-à-vis the Mexican nationalist discourse - Iturriaga Acevedo, Eugenia (Cultura y Representaciones Sociales, 2019)
After the 1910 Revolution, Mexico adopted in its discourse an assimilation policy in which the mestizo was transformed into the official historical leading character thereby conceiving a single way of being Mexican. This paper aims to show how the “Maya” was, and has been used, in the construction of Yucatecan regionalism and how this regionalism is a response to the national homogenizing project. Yucatecan regionalism has been accompanied by a pride that is nourished by an ambivalent relationship with “the Maya” (admiration and disdain) and a marked distance from the political center of the country and its mestizo discourse. It is also shown how both, nationalism and regionalism, use the same resources to shape identities and how these are transformed over time.